Alkaloids from the roots of Stemona tuberosa and their anti-tobacco mosaic virus activities. Issue 12 (22nd March 2019) - Hu, Zhan-Xing; Tang, Hong-Yu; Guo, Jie; Aisa, Haji Aker; Zhang, Yu; Hao, Xiao-Jiang
Abstract: Stemtuberlines A (1 ) and B (2 ), two new alkaloids with a unique tricyclic pyrrolo [3, 2, 1- jk ]benzazepine-12-one nucleus, three new croomine-type alkaloids, stemtuberlines C-E (3 –5 ), together with seven known ones were isolated from the roots of Stemona tuberosa . The structures of the new alkaloids were elucidated based on a comprehensive spectroscopic data analysis. The absolute configurations of1 and2 were determined by quantum ECD calculations. The anti-tobacco mosaic virus activity of the Stemona alkaloids was firstly evaluated and compound11 exhibited significant anti-tobacco mosaic virus activity with the curative inhibition rate of 84.6% at concentration of 50  μ g/mL. Graphical abstract: Image 1